Universality Without Uniformity: A Culturally Inclusive Approach to Sensitive Responsiveness in Infant Caregiving. Issue 3 (4th April 2017) - Mesman, Judi; Minter, Tessa; Angnged, Andrei; Cissé, Ibrahima A. H.; Salali, Gul Deniz; Migliano, Andrea Bamberg
Abstract : Do caregivers in non‐Western communities adapt their behaviors to the needs of infants? This question reflects one of the most long‐standing debates on the universality versus culture‐specificity of caregiver–infant interactions in general and sensitive responsiveness to infants in particular. In this article, an integration of both points of view is presented, based on the theoretical origins of the sensitive responsiveness construct combined with the ethnographic literature on caregivers and infants in different parts of the world. This integration advocates universality without uniformity, and calls for multidisciplinary collaborations to investigate the complexities and nuances of caregiver–infant interactions in different cultures. Salient issues are illustrated with observations of infants (ages 7–31 months) in Mali, the Republic of Congo, and the Philippines.